Effects of sulfadiazine and Cu on soil potential nitrification and ammonia-oxidizing archaea and bacteria communities across different soils - Hou, Guoqin; Wazir, Zafran Gul; Liu, Jing; Wang, Guizhen; Rong, Fangxu; Xu, Yuzhi; Li, Mingyue; Liu, Kai; Liu, Aijv; Liu, Hongliang; Wang, Fayuan (Frontiers in Microbiology, 2023)
Introduction Sulfadiazine (SDZ) and copper (Cu) are frequently detected in agricultural soils, but little is known on their single or combined impact on ammonia oxidizing microbial community and function across different soils. Methods In this study, a microcosm was conducted to distinguish the microbial ecotoxicity of SDZ and Cu across different soils by analyzing soil potential nitrification rate (PNR) and the amoA gene sequences. Results The results showed that the single spiking of SDZ caused a consistent decrease of soil PNR among three tested soils, but no consistent synergistic inhibition of SDZ and Cu was observed across these soils. Moreover, across three tested soils, the distinct responses to the single or joint exposure of SDZ and Cu were found in amoA gene abundance, and diversity as well as the identified genus taxa of ammonia-oxidizing archaea (AOA) and bacteria (AOB). Meanwhile, only the specific genus taxa of AOA or AOB consistently corresponded to the variation of soil PNR across different treated soils. The further principal component analysis (PCA) exhibited that the variable influence of SDZ and Cu on ammonia oxidizing microbial community and function was greatly dependent on soil type. Discussion Therefore, in addition to ecological functionality and the specific prokaryotic taxa, soil microbial ecotoxicity of SDZ and Cu also was dependent on edaphic factors derived from soil types. This study proposes an integrative assessment of soil properties and multiple microbial targets to soil contamination management.